Assessment of performance compliance with construction site safety management system in Klang Valley, Malaysia - Mohammed, Yakubu Danasabe (2015)
In most construction sites, poor safety awareness is a major factor affecting workers’ performances at the workplace. Safety management is associated with the policies, objectives, procedures, methods, roles and functions that aim at controlling hazards and risk in socio-technical systems. Construction workers accidents and fatalities rate in construction industries is attributed to the non compliance by contractors toward health and safety regulation on construction sites. The regulatory systems and standard are in the form of occupational safety and health laws. The regulatory system and standard are built on the fact that the accidents and fatalities at construction sites may be mitigated by good construction practice, effective site inspection and strict enforcement of high standard of care. The awareness and perception of workers to safety, health and their working environment are an important aspect to enhance the cares of building construction at construction sites. This research examines the effectiveness of safety management system and explored the relationship between safety management aspect and workers’ compliance to safety management system. In order to determine the effectiveness or ineffectiveness of the system on site, a comparative cross – sectional study was conducted in 20 construction sites in Klang valley in order to assess the pattern of injuries or accidents among construction workers, contractor’s performance regarding safety and health elements in construction site and the level of compliance by the construction firms. Using cluster sampling method 344 construction workers were sampled from the 20 construction sites, using a structured questionnaire with compliance to construction sites safety measures. A descriptive analysis of the comparative cross – sectional study was computed. The results show that poor implementation of safety and health measures on the site is responsible for the occurrence of accidents among workers. The injuries or accidents on site can be reduced to a certain level with precautionary measures as regard to safety and health is put in place. Effective assessment of contractor’s performance regarding safety and health practices in construction sites, OSHA standardized mathematic formula was used. The result of the analysis show that the rate of accidents increases with inadequate number of workers at work place. This situation can be reduced or eliminated with regulatory measure in terms of number of employees on site. In order to determine the level of compliance of the construction sites to safety management system, safety and health assessment system in construction (SHASSIC) was used. The results show that 55%, representing firms within (55 – 69) ranking as 3 – star were all potential and significant workplaces, high risks or hazards are managed and documented. However, there are few low risk work activities that are neglected, due to poor compliance to safety measure on the sites by contractors. The relationship between safety management system and workers’ compliance was correlated and the result was found to be significant (P < 0.005). This association was modeled using simple linear regression and from those models the results show that the more compliance to safety management system by the workers the better the benefit of safety management system on construction sites. This study provided substantial evidences that laws and regulations alone do not ensure safety and health practices at construction sites. In fact, that what is required is the aspect of adoption and implementation of safety – conscious contractors which supported by experience and trained employees. The findings of this study will provide good guidance to assist contractors in developing effective and efficient health and safety management system in the Klang valley construction industry. The comparative cross – sectional study should help in achieving an improvement on construction site safety performance.